Polymorphism of the oestrogen receptor (ESR) gene in some pig breeds reared in Vietnam - Thúy Lê Thị; Minh, Lưu Quang; Thủy Trần Thu; Bình Nguyễn Trọng; Lân Phạm Doãn; Vang Nguyễn Đăng (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 45-50, 2005